Pengaruh Tingkat Partisipasi Angkatan Kerja (TPAK),Jumlah Penduduk, Dan Upah Minimum Terhadap Pertumbuhan Ekonomi di Provinsi Banten - Disti Macela Putri; M.Afdal Samsuddin (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2025)
This study aims to analyze the effect of labor force participation rate, population, and minimum wage on economic growth in Banten Province as measured by Gross Regional Domestic Product (GRDP). This study uses panel data from 8 regencies/cities during the period 2017-2018 and is analyzed using the panel data regression method. Based on the results of the Chow, Hausman, and Lagrange Multiplier tests, the best model used is the Random Effect Model (REM). The results of the analysis show that simultaneously, the three independent variables have a significant effect on economic growth. However, partially only the Minimum Wage variable has a positive and significant effect on GRDP, while the TPAK and Population variables show a negative effect and are not statistically significant.